FOOD DEMAND ESTIMATION AND ALTERNATIVE MEASUREMENT OF REGIONAL POVERTY LINE FROM HOUSEHOLD SURVEY DATA IN INDONESIA - Sunaryati, . (Buletin Studi Ekonomi; Vol 17.No.2.Agustus 2012 (PP.99-225), 2012)
Abstract : Food Demand Estimation and Alternative Measurement of Regional Poverty Line from Household Survey Data in Indonesia. The purpose of this paper is to analyze food demand behaviour of  Indonesian households and alternative measurement of regional poverty line using Linear Expenditure System (LES).  This paper uses cross section data about household’s expenditure from the 2007 Indonesian Life Family Survey (IFLS,2007), a nationwide survey conducted in 2007. The results show that the Indonesian households have the maximum marginal budget share on rice and the minimum one on fish. From this finding, Indonesian households could be called as “rice lovers” households. Furthermore, results also show that the highest poverty line is for Banten and the lowest poverty line is for  East Kalimantan; the minimum average household expenditure is for  Nusa Tenggara Barat and the maximum is for East Kalimantan. Abstrak: Estimasi Permintaan Makanan dan Alternatif Pengukuran Garis Kemiskinan Daerah dari Data Survei Rumah tangga di Indonesia . Tujuan makalah ini adalah untuk menganalisis perilaku permintaan makanan rumah tangga Indonesia dan pengukuran alternatif garis kemiskinan daerah menggunakan Sistem Pengeluaran Linear (LES). Makalah ini menggunakan data cross section tentang pengeluaran rumah tangga dari Survei Kehidupan Keluarga Indonesia 2007 (IFLS, 2007), survei nasional dilakukan pada tahun 2007. Hasil penelitian menunjukkan bahwa rumah tangga Indonesia memiliki pangsa anggaran maksimum yang berlaku pada beras dan yang minimum pada ikan. Dari temuan ini, rumah tangga bahasa Indonesia bisa disebut sebagai rumah tangga "pecinta nasi". Selanjutnya, hasil penelitian juga menunjukkan bahwa garis kemiskinan tertinggi adalah untuk Banten dan garis kemiskinan terendah adalah Kalimantan Timur, pengeluaran rata-rata minimum rumah tangga adalah untuk Nusa Tenggara Barat dan maksimal adalah untuk Kalimantan Timur.
Keywords: Permintaan Makanan, Garis Kemiskinan Daerah, Sistem Pengeluaran Linear (LES), IFLS.